(untitled) (Revista de Medicina Clinica, 2023)
Lung cancer and non-Hodgkin lymphoma are responsible for up to 85-90% of malignant disease-related superior vena cava syndromes, while metastatic cancers account for approximately 10%. In order to review the pathophysiology, etiology, clinic, diagnosis and treatment, we present a patient who presented with superior vena cava syndrome as an initial presentation due to previously undiagnosed lung cancer.